Characteristics of gastrointestinal stromal tumours, diagnostic procedure and therapeutic management and main directions of nursing practice in gastrointestinal stromal tumours - Wiraszka, Grażyna R.; Głuszek, Stanisław; Kozieł, Dorota (Contemporary Oncology/Współczesna Onkologia, 2014)
Gastrointestinal stromal tumours (GIST) constitute a separate group of mesenchymal neoplasms of the gastrointestinal tract. They have been commonly recognized for a few years, they have created a new problem in medical practice. GIST are more often centred in the stomach. They equally affect female and male patients and occur mainly in patients older than 50 years of age. The clinical picture of the tumour is non-specific. Radical surgical treatment and molecularly targeted therapy with tyrosine kinase inhibitors are used in GIST treatment. Nursing practice with reference to GIST danger is connected with biopsychosocial interventions of perioperative, oncological and palliative procedures and involves the area of health education mainly oriented towards shaping preventive procedures which favour early disease detection and support therapy and recovery.